Epizootological study on Toxoplasma gondii in zoo animals in the Czech Republic - Bártová, Eva; Lukášová, Radka; Vodička, Roman; Váhala, Jiří; Pavlačík, Lukáš; Budíková, Marie; Sedlák, Kamil (Acta tropica, 2018)
Toxoplasma gondii is protozoan parasite with ability of causing disease in wide-spectrum of animals; many species of animals in captivity died of clinical toxoplasmosis. The monitoring of T. gondii antibodies in zoo animals can be an important indicator of T. gondii circulation in zoo. The aim of this study was to examine sera of animals from eight Czech zoos by latex agglutination test with statistical evaluation and detect T. gondii DNA in stray cats and rodents captured in the zoos. T. gondii antibodies were detected in 33% of 1043 zoo animals without statistical difference between birds (27%, n = 74) and mammals (33%, n = 969). In birds, the chance to be infected with T. gondii was higher in Accipitriformes (71%) compared to Pelecaniformes (6%) (p < 0.0001). In mammals, the chance to be infected with T. gondii was higher in Carnivora (63%) compared to Cetarodactyla (30%), Perissodactyla (26%), Primates (28%) and Rodentia (13%) (p < 0.0001) and higher in Felidae (70%) compared to Bovidae (28%) and Equidae (28%) (p < 0.0001). Mammals with carnivore/scavenger way of feeding were in a higher risk of T. gondii infection compared to herbivores and omnivores (p < 0.0001). T. gondii DNA was detected in tissue of one stray cat while in none of 77 rodents caught in zoo. This study is the first report on toxoplasmosis in zoos from the Czech Republic including seroepidemiology and molecular detection.
Keywords: protozoální DNA; protilátky protozoální; hlodavci; LAT; Serology; Toxoplasma; Seroepidemiologic Studies; Mammals; séroepidemiologické studie; Risk Factors; kočky; Rodentia; Česká republika; Animals, Wild; Animals, Zoo; divoká zvířata; Antibodies, Protozoan; DNA, Protozoan; Czech Republic; savci; Toxoplasmosis, Animal; PCR; ptáci; Birds; Animals; zvířata v ZOO; Toxoplasmosis; Latex Fixation Tests; latex fixační testy; zvířata; rizikové faktory; Stray cats; Carnivora; toxoplazmóza zvířat; Cats